Soil Characteristics of Padma Multipurpose Bridge (MIST International Journal of Science and Technology, 2022)
Padma Multipurpose Bridge is situated on a section of the Padma river where the soil condition is highly heterogeneous and intermixed with different soil layers, for which pile design was the critical part. This paper describes the soil properties and ground profiling of the Padma Multipurpose Bridge. Different types of field and laboratory tests were carried out to obtain accurate soil parameters and ground profiles along the whole alignment of the bridge. Standard Penetration Tests, Cone Penetration Tests, and grain size analyses were conducted for the soil classifications and ground profiling. Flat Plate Dilatometer Tests, High Pressure Dilatometer Tests, and Self-Boring Internal Friction Tests were performed to obtain the stiffness of the different soil layers and shear strength parameters in field conditions. Cross-hole and Seismic Tomography Geophysical tests were executed to obtain seismic waves and dynamic shear modulus of each soil layer. Gel Push Soil Sampling technique was used to collect undisturbed samples of sandy soils to get accurate stress–strength-dilatancy characteristics of sandy soils through different laboratory tests. The soil was classified into three Units and some sub-units based on grain size and SPT-N value. Soil parameters were finalized based on both laboratory and field test results. The pile design was possible for accurate measurement of soil parameters and ground profiling along the alignment of the bridge.MIJST, Vol. 10, November 2022 (Special Issue: Padma Bridge): 33-41